Pembuatan Sistem Informasi Geografis Pemetaan Daerah Asal Mahasiswa Politeknik Aceh Selatan - Darma Setiawan Putra; Alfahri Hariza; Fardiansyah (Jurnal Inotera, 2021)
Nowadays, information is an essential element in life because every human activity and business needs it. One of the essential forms of information is geographic information that is used in the field of education. Geographic information is defined as a collection of data and facts about the phenomena of the earth, land, and its inhabitants in space and time. The geographical location of the South Aceh Polytechnic student's homeland is an essential data. If this information is managed properly, the leadership can find out the distribution of data from the students' homeland. The author designs and builds a Geographic Information System to manage student data from the South Aceh Polytechnic to find out the distribution of the homeland of the South Aceh Polytechnic students.This information system is designed using the PHP programming language with the CodeIgniter 3 Framework, MySQL, and the LeafletJS JavaScript Library. Testing the system using the Blackbox method. The results indicate that the system can run well by displaying markers of students' homeland on the map so that this information system can be utilized to determine the distribution of students' homeland effectively and efficiently.